The Role Of Social Media In The Promotion Of Urdu Language And Literature - Dr. Zahid Akhtar Shaheen , Dr. Shazia Andleeb , Sehar Asghar , Saman Saleem (Migration Letters, 2024)
The advanced form of media is Social Media. Social Media is not only important for society, human behavior and daily routines, but it is also very important for the development of Urdu language and literature. It is possible to r[1]each the whole world due to social Media. Urdu language has been accepted all over the world and Urdu literature has spread to the corners of the world. People of the other communities and those who understand other languages can also understand Urdu literature using Social Media. Social Media apps like face book, insta gram, you tube, twitter, goggle, what’s app, telegram, zoom, meet, tik tok,snap chat, imo play important role to spread Urdu language and literature.